Pengaruh Persepsi Harga dan Promosi Terhadap Keputusan Pembelian Lensa Kontak Pada Diens Optik Purwakarta - Puspasari, Dewi; Amalia, Dinda; Pamungkas, Eko Wiji; Hendraliany, Srie; Fitriani, Dini (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This study aims to investigate the influence of price perception and promotion on purchasing decisions of contact lenses at Diens Optik Purwakarta. The optical business faces intense competition, necessitating effective strategies to attract and retain consumers. Price perception and promotional strategies play crucial roles in consumer purchase decisions. Diens Optik Purwakarta utilizes various promotional techniques, including shopkeeper and door-to-door approaches, alongside a 10% discount on purchasing three products as a retention strategy. Despite these efforts, recent months have seen a decline in consumer numbers. Using a quantitative approach under positivism philosophy, the study gathered data from 97 respondents through incidental sampling. Validity tests were conducted using the product-moment correlation coefficient method. Results indicated high validity for all items related to price perception and promotion. Statistical analysis revealed significant positive influences of both price perception and promotion on purchasing decisions